Evaluation of Microleakage in Zirconomer®: A Zirconia Reinforced Glass Ionomer Cement - Rawan Albeshti; Saroash Shahid (University of Zagreb. School of Dental Medicine, 2018)
Objective: To evaluate the microleakage of four direct restorative materials. Materials and Methods: Sixteen sound bovine incisors were chosen and randomly divided into four groups; Group I-Zirconomer, Group II-KetacTM Silver, Group III-FiltekTM Z500 (composite) and Group IV-Dispersalloy® (amalgam). Seven proximal (mesial & distal) cavities, for each material were prepared and restored. All restored samples were stored in 37oC distilled water for 24 hr and then subjected to thermo-cycling process at temperatures between 5-55oC. The samples were immersed in dye solution of 0.5% methylene blue for 24 hr. Each filled cavity was sectioned through the centre of restoration and then studied under a stereomicroscope to assess the marginal leakage. The obtained microleakage scores were statistically analysed. Results: The highest mean score of leakage was recorded in Group II-KetacTM Silver followed by Group I-Zirconomer and Group III-FiltekTM Z500 (composite). The lowest mean score of dye penetration was verified in Group IV-Dispersalloy® (amalgam). Statistically, there were significant differences between Zirconomer and other groups of KetacTM Silver and amalgam, whereas the Zirconomer groups had no significant differences with composites. All tested groups showed significant differences with amalgam restorations. Conclusions: The marginal leakage was evident in all restorative materials. Further studies with clinical trial have to be done.